Explaining Factors of Job Pursuit Intention in Indonesian Military Institution - Syaebani, Muhammad Irfan; Anoviar, Alia Noor; Pusparini, Elok Savitri; Rachmawati, Riani (Department of Management, Faculty of Economics and Business, Brawijaya University, 2015)
Reformation brought many changes in public sectors in Indonesia, one of them is Military institution. Reformation required Military to become professional in every organizational aspects, including human resources as a part of resource that need to be manage strategically.Â Proficient and competent human resource will help organization reach its vision, missons, and strategic goals. One of the strategy to attract competent human resource is to design the recruitment and selection process in talent management corridor, where organization must identify factors which attracting a candidate to join into organization or simply called job pursuit intention. To find out what factors lead to job pursuit intention into military institution in Indonesia, data was collected using qualitative approach from middle-rank military officer. Their past experiences concerning motives/factors which lead them joined into military were explored. From analysis, it reveals that there are 5 factors which make them joined military; employer familiarity, subjective fit, hiring expectation, economic motive, and nationalism/patriotism motive.